2010
DOI: 10.1111/j.1365-2761.2009.01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between growth and disease resistance in rainbow trout, Oncorhynchus mykiss (Walbaum)

Abstract: Rainbow trout from 23 families were evaluated for growth and resistance to the bacterial coldwater disease (BCWD) caused by Flavobacterium psychrophilum and infectious haematopoietic necrosis (IHN) caused by IHN virus. Average family weights were between 161 and 263 g with an average of 225 g at 213 days post-fertilization with specific growth rates ranging from 2.37 to 2.88. Per cent survival of fish challenged with F. psychrophilum was between 18% and 100%, while for those challenged with IHNV, the range was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 34 publications
(49 reference statements)
1
22
2
1
Order By: Relevance
“…However, it is unclear whether there is a relationship between fish length at a specific age and IHNV resistance. Overturf et al (2010) examined the phenotypic correlation between size and resistance to IHNV in rainbow trout and only found a positive correlation for older fish (213 d post-fertilization, 224.7 g), but not for younger fish. Additionally, Barroso et al (2008) determined that the 2 traits were genetically independent in rainbow × Yellowstone cutthroat trout crosses.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is unclear whether there is a relationship between fish length at a specific age and IHNV resistance. Overturf et al (2010) examined the phenotypic correlation between size and resistance to IHNV in rainbow trout and only found a positive correlation for older fish (213 d post-fertilization, 224.7 g), but not for younger fish. Additionally, Barroso et al (2008) determined that the 2 traits were genetically independent in rainbow × Yellowstone cutthroat trout crosses.…”
Section: Methodsmentioning
confidence: 99%
“…Host genetic diversity and stochasticity in the viral entry process are often hypothesized as the main factors driving variation in viral burdens between hosts (Brault et al, 2010; Capparelli et al, 2009; Fellay et al, 2007; Howey et al, 2009; Kaslow et al, 2005; Matthews et al, 2006; Overturf et al, 2010; Pelak et al, 2010). However, many systems are limited in their ability to explicitly quantify the role of these factors in regulating viral load variation.…”
Section: Introductionmentioning
confidence: 99%
“…The survival range of 0 to 94.74% against edwardsiellosis observed in rohu families in the present study also indicated a wide variation in their susceptibilities to the disease. Similar observations were also made in Atlantic salmon (Salmo salar) challenged with A. salmonicida (Marsden et al 1996;Odegard et al 2006), rohu challenged with A. hydrophila (Sahoo et al 2004) psychrophilum in rainbow trout (Silverstein et al 2009;Overturf et al 2010). Disease resistance can be evaluated through different traits/tests obtained from a controlled challenge study.…”
Section: Discussionmentioning
confidence: 53%